TRAP-Induced Platelet Reactivity Is Inhibited by Omega-3 Fatty Acid-Derived Prostaglandin E3 (PGE3) - José-Miguel Osete; Faustino García-Candel; Francisco-José Fernández-Gómez; Miguel Blanquer; Noemí M. Atucha; Joaquín García-Estañ; David Iyú (Biomedicines)
Background: Prostaglandins are naturally occurring local mediators that can participate in the modulation of the cardiovascular system through their interaction with Gs/Gi-coupled receptors in different tissues and cells, including platelets. Thrombin is one of the most important factors that regulates platelet reactivity and coagulation. Clinical trials have consistently shown that omega-3 fatty acid supplementation lowers the risk for cardiovascular mortality and morbidity. Since omega-3 fatty acids are the main precursors of PGE3 in vivo, it would be relevant to investigate the effects of PGE3 on Thrombin Receptor Activating Peptide (TRAP-6)-induced platelet reactivity to determine the receptors and possible mechanisms of action of these compounds. Methods: We have measured platelet aggregation, P-selectin expression, and vasodilator-stimulated phosphoprotein (VASP) phosphorylation to evaluate platelet reactivity induced by TRAP-6 to determine the effects of PGE3 on platelet function. Results: We assessed the ability of DG-041, a selective prostanoid EP3 receptor antagonist, and of ONO-AE3-208, a selective prostanoid EP4 receptor antagonist, to modify the effects of PGE3. PGE3 inhibited TRAP-6-induced platelet aggregation and activation. This inhibition was enhanced in the presence of a Gi-coupled EP3 receptor antagonist and abolished in the presence of a Gs-coupled EP4 receptor antagonist. The effects of PGE3 were directly related to changes in cAMP, assessed by VASP phosphorylation. Conclusions: The general effects of PGE3 on human platelet reactivity are the consequence of a balance between activatory and inhibitory effects at receptors that have contrary effects on adenylate cyclase. These results indicate a potential mechanism by which omega-3 fatty acids underlie cardioprotective effects.